Simple Renal Cysts: Prevalence, Associated Risk Factors and Follow-Up in a Health Screening Cohort - Ozveren, Bora; Onganer, Efe; Türkeri, Levent N. (Urology Journal, 2016)
Purpose: To investigate the prevalence of simple renal cysts in an adult health-screening cohort, and to evaluate clinical characteristics, associated risk factors and the natural course. Materials and Methods: Between April and November 2008, a thousand individuals diagnosed with simple renal cyst by ultrasonography in a check-up program were chart-reviewed for demographic-clinical characteristics and cyst features. Follow-up was done via electronic patient records. Univariate and multivariate analyses to evaluate the relationship of outcomes and correlation analysis were done to measure the degree of association between parameters. Results: The prevalence was 7.7%. There were 123 cysts in 77 patients, followed for 3.5 years (mean). Individuals with cysts were older (P < .01). Prevalence rates were 2.7% in individuals younger than 40 years and 23.9% in older than 60. The cysts were predominantly (94.8%) detected in males and most (63.6%) were solitary. No relation with Body Mass Index and total cholesterol levels was found but serum creatinine values were significantly increased in individuals with cysts (P < .01). There was no difference in the diagnosis of hypertension and microscopic hematuria in patients with renal cysts, however diabetes/hyperglycemia were more common and increasing age correlated with higher number of cysts (all P < .05). Follow-up revealed that the number of cysts were increased and/or the same in 86.5%; the sizes of cysts were larger and/or the same in 78.4% of patients, while in 14% of patients the cyst disappeared. Conclusion: In a cohort of adults undergoing a health-screening, the prevalence of simple renal cyst was found 7.7% by ultrasonography. Renal cysts were more common in males and elders, and associated with increased levels of serum creatinine and diabetes.